ASSOCIATION OF HBA1C AND NEUTROPHIL LYMPHOCYTE RATIO WITH NORMAL-TENSION GLAUCOMA IN METABOLIC SYNDROME AND OBSTRUCTIVE SLEEP APNEA RISK PATIENTS - Seskoati Prayitnaningsih (University of Brawijaya, 2021)
Background: Normal-Tension_Glaucoma (NTG) is an eye disease and characterize with low intraocular pressure (IOP) levels. In population-based settings, the diagnose of glaucoma is based on the IOP levels of 21 mmHg, and its usually delayed. A recent study HbA1c levels could lead to IOP changes. Obstructive Sleep Apnea (OSA) result oxidative stress that results an altered function of neutrophil in patients with NTG.